2009
DOI: 10.4067/s0717-95022009000400030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Albendazole Sulphoxide on Embryonic, Foetal and Placental Parameters in Wistar Rats

Abstract: SUMMARY:The aim of this work was to evaluate the effect of albendazole sulphoxide (ABZSO), administered to Wistar rats during pregnancy on embryonic, foetal and placental parameters. A colpocytological control was performed daily and detection of spermatozoa in the vaginal smear was considered as day 0 of pregnancy. For the preimplantational study, ABZSO (10 mg/kg) was orally administered at day 2 of pregnancy; at day 4 the embryos were collected. For the postimplantational study, ABZSO (10 mg/kg) was orally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The embryotoxic and teratogenic effects of ABZ when administered to pregnant animals have been demonstrated. ABZ has been shown to produce increased resorption, decreased birth weight, teratogenic effects, such as external, skeletal and vascular abnormalities, when administered during gestation in mice, rats, rabbits, sheep and zebrafish (Capece et al., ; Carlsson, Patring, Erik Ullerås, & Oskarsson, ; Cristòfol et al., ; Navarro, Cristòfol, Carretero, Arboix, & Ruberte, ; Teruel, Felipe, Solana, Sallovitz, & Lanusse, ; Teruel et al., ). Most of the ABZ toxicity studies have been carried out in mammals, with few data in birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The embryotoxic and teratogenic effects of ABZ when administered to pregnant animals have been demonstrated. ABZ has been shown to produce increased resorption, decreased birth weight, teratogenic effects, such as external, skeletal and vascular abnormalities, when administered during gestation in mice, rats, rabbits, sheep and zebrafish (Capece et al., ; Carlsson, Patring, Erik Ullerås, & Oskarsson, ; Cristòfol et al., ; Navarro, Cristòfol, Carretero, Arboix, & Ruberte, ; Teruel, Felipe, Solana, Sallovitz, & Lanusse, ; Teruel et al., ). Most of the ABZ toxicity studies have been carried out in mammals, with few data in birds.…”
Section: Discussionmentioning
confidence: 99%
“…However, ABZ is currently being extra‐label used in avian production systems. Toxicological studies in both farm and laboratory animals have shown ABZ and its active sulphoxide metabolite (ABZSO) to be embryotoxic/teratogenic (Delatour, Garnier, Benoit, & Longin, ; Teruel, García, & Catalano, ). The pharmacokinetic behaviour and tissue residue depletion of these anthelmintics have been well reported in ruminant species.…”
Section: Introductionmentioning
confidence: 99%
“…The second group was given 7.5 mg/kg bwt of ricobendazole subcutaneous injection once. These doses were calculated according to oral dose recorded by Teruel et al, (2009). The third group was given 7.5 mg/kg bwt of ricobendazole subcutaneous injection, twice with 3 week intervals.…”
Section: Experimental Designmentioning
confidence: 99%
“…Although flubendazole is the only BZD approved for parasite control in poultry, albendazole (ABZ) is frequently extra-label used for this purpose in avian species. Toxicological studies in both farm and laboratory animals have shown ABZ and its active sulphoxide metabolite (ABZSO) to be embryotoxic/teratogenic (Delatour et al, 1984, Teruel et al, 2009). The goal of the work reported here was to evaluate the effect of ABZ treatment on the fertility and hatchability of eggs collected from treated breeder hens.…”
Section: Introductionmentioning
confidence: 99%